Ethical conflicts and their characteristics among critical care nurses - Lluch-Canut, Teresa (Nursing ethics, 2020)
Introduction:Ethical conflict is a phenomenon that has been under study over the last three decades, especially the types moral dilemma and moral distress in the field of nursing care. However, ethical problems and their idiosyncrasies need to be further explored.Aim:The objectives of this study were, first, to obtain a transcultural Portuguese-language adaptation and validation of the Ethical Conflict Nursing Questionnaire–Critical Care Version and, second, to analyse Portuguese critical care nurses’ level of exposure to ethical conflict and its characteristics.Methods:A cross-cultural validation and descriptive, prospective and correlational study. The sample was made for 184 critical care nurses in 2016.Ethical Considerations:The study was authorised by Bioethics Commission of the University of Barcelona, the Associaçâo de Apoio ao Serviço de Cuidados Intensivos do Centro Hospitalar do Porto and the Sociedade Portuguesa de Enfermagem de Saúde Mental.Findings:The Portuguese version of the Ethical Conflict Nursing Questionnaire–Critical Care Version was a valid and reliable instrument to measure exposure to conflict. Moral outrage was the most common type of conflict. The most problematic situations were the ineffectiveness of analgesic treatments, the administration of treatments considered futile and the mismanagement of resources.